2020
DOI: 10.3390/biology10010010
|View full text |Cite
|
Sign up to set email alerts
|

A New Transmission Route for the Propagation of the SARS-CoV-2 Coronavirus

Abstract: Background: Starting late 2019, a novel coronavirus spread from the capital of the Hubei province in China to the rest of the country, then to most of the world. To anticipate future trends in the development of the pandemic, we explore here, based on public records of infected persons, how variation in the virus tropism could end up in different patterns, warranting a specific strategy to handle the epidemic. Methods: We use a compartmental model to describe the evolution of an individual through several poss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The other important information is that, as discovered by Danchin et al [4], an alternative transmission way may occur. Here, it is due to the proportion of asymptomatic infected individuals that is not negligible, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The other important information is that, as discovered by Danchin et al [4], an alternative transmission way may occur. Here, it is due to the proportion of asymptomatic infected individuals that is not negligible, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 96%
“…They opined that to reduce R 0 significantly, the government should continue implementing strict measures on containment and public health issues. In the same tune as the latter, the model of Danchin et al [4] also suggests continuing to implement effective quarantine measures to avoid a resurgence of infection. The model consists of five (5) compartments: susceptible, infected, alternative infection, detected, and removed.…”
Section: Introductionmentioning
confidence: 99%
“… 38 , 39 , 40 It has been suggested that possible fecal-oral route is through the active replication within the gastrointestinal tract followed by the release of virions in the wastewater streams and sewers. 41 Because the viral particles from the infected patients are usually mixed with organic matter, such as sputum and feces, and are thereby protected, the disinfection mechanism seems to be ineffective. 41 …”
Section: Occurrence and Survival Of Covid-19 In Wastewater Urine And Biosolidsmentioning
confidence: 99%
“… 41 Because the viral particles from the infected patients are usually mixed with organic matter, such as sputum and feces, and are thereby protected, the disinfection mechanism seems to be ineffective. 41 …”
Section: Occurrence and Survival Of Covid-19 In Wastewater Urine And Biosolidsmentioning
confidence: 99%
“…Ineffective treatment techniques coupled with poor quality control of existing infrastructure means that these viruses have more avenues to persist in the environment. It has been pointed out that SARS-CoV-2 could utilize these water bodies as potential environmental reservoirs, and considering the high rate of infectivity, it would be a serious issue to deal with in these countries (Danchin et al 2020). An important counterpoint to note is that despite the putative assumptions and circumstantial evidence, there has not been any concrete evidence for the presence of active SARS-CoV-2 virions in wastewater, but only of fragmented particles, in particular RNA (Ahmed et al 2020;Wu et al 2020;Kumar et al 2020;Fongaro et al 2021;Medema et al, 2021;Kolarević et al 2021;Tanhaei et al 2021).…”
Section: Sars-cov-2 As a Potential Enteric Virus: Environmental Persistence And Further Scope Of Infection Through Wastewatermentioning
confidence: 99%